2015
DOI: 10.1016/j.fuproc.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Structural transformation of nascent char during the fast pyrolysis of mallee wood and low-rank coals

Abstract: The changes in char structure during the fast pyrolysis of three different feedstocks from 600°C to 1200°C were investigated. Western Australian Collie sub-bituminous coal, Victorian Loy Yang brown coal and Australian mallee wood were pyrolysed in a wire-mesh reactor at a heating rate of 1000 K s −1 with holding time ranging from 0 s to 50 s. FT-Raman/IR spectroscopy was used to characterise the structural features of the chars obtained at different temperatures. The combined use of a wire-mesh reactor and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The same conclusion was reached in the study of Zhang et al. [100,101] Lievens et al [112] reported the structure of Inner Mongolia low-rank coal, concluding that its aromatic ring structures consisting of 59% amorphous structures (G L , G, G R , V L , and V R bands), 22% highly ordered structures with no less than six rings (D band), 16% aromatic structures characterized by aliphatic and/or ether substitutions (S L , S bands), and 3% substituted benzene rings (S R , R bands).…”
Section: Study Of Coal's Functional Groupssupporting
confidence: 85%
See 1 more Smart Citation
“…The same conclusion was reached in the study of Zhang et al. [100,101] Lievens et al [112] reported the structure of Inner Mongolia low-rank coal, concluding that its aromatic ring structures consisting of 59% amorphous structures (G L , G, G R , V L , and V R bands), 22% highly ordered structures with no less than six rings (D band), 16% aromatic structures characterized by aliphatic and/or ether substitutions (S L , S bands), and 3% substituted benzene rings (S R , R bands).…”
Section: Study Of Coal's Functional Groupssupporting
confidence: 85%
“…In recent years, some researchers [100][101][102][103][104][105][106][107][108][109][110][111][112] studied the structure of coal by using Raman spectroscopy and referring to the curve-fitting method by Li et al [53,86,87] Zhang et al [100,101] considered the structural changes of semicoke during the rapid pyrolysis of wood and low-rank coal at 600-1,200 C and got similar result of Li et al Wang et al [102] reported that the A…”
Section: Study Of Coal's Functional Groupsmentioning
confidence: 94%
“…The preparation and the properties of coal samples have been described in ref . The nascent chars, which are prepared for the measurement of AAEM concentration, chemical structure, and char–O 2 reactivity, were produced under the same experimental conditions as those in ref . Briefly, the heating rate was chosen as 1000 K s –1 to achieve fast pyrolysis.…”
Section: Methodsmentioning
confidence: 99%
“…For Collie coal char, AAEM species showed the negligible effect on the nascent char–O 2 reactivity for the char prepared at 600 °C. Nevertheless, with the fast transformation of nascent char structure during pyrolysis from 600 to 1200 °C, , the roles of AAEM species and char structure on char–O 2 reactivity is still unclear, which arouse the motivation of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous physicochemical techniques such as Brunauer–Emmett–Teller measurements, Fourier transform infrared spectroscopy, solid-state nuclear magnetic resonance, X-ray diffraction (XRD), Raman, and so on have been applied to study the structural features of coal char and provided useful information during pyrolysis. Raman spectroscopy is being more and more widely used to characterize the microstructure of crystalline and amorphous carbon materials due to their high efficiency, nondestructive nature, and high precision. , Li and his group compared the Raman spectroscopy of condensed aromatic compounds with the chars and identified the deconvoluted peaks of chars, and the identification method has been used to characterize the chemical structure of chars produced from low-rank coals and biomass during pyrolysis and gasification. Xu used the identification method of Li to study the relationship between coal structures and combustion characteristics and found that the Raman spectral parameters can act as a good indicator for coal combustion characteristics.…”
Section: Introductionmentioning
confidence: 99%